Variáveis associadas ao envelhecimento cerebral bem-sucedido em uma amostra de idosos muito idosos da comunidade - Karoline Carvalho Carmona (2018)
Background: Successful brain aging is a condition in which there is little, or no cognitive decline compared to younger adults. Thus, beyond the mere absence of disease and preserved functionality, there are individuals who stand out for outperforming what is considered normal for age on cognitive tests. We still do not have sufficient studies investigating the sociodemographic and biological variables that favor such elderly. Objectives: To investigate sociodemographic and lifestyle aspects of individuals aged 75+ years and cognitive performance similar to younger healthy elderly (60-69 years). Methods: In the Pietà study, a population-based investigation conducted in Caeté (MG), we evaluated 639 elderly individuals aged 75 years. After cognitive screening using the Mini-Mental State Examination, Brief Cognitive Battery and the Pfeffer Questionnaire, 132 healthy elderly subjects were identified (age: 79.8 ± 4.5 years; education: 3.0 ± 2.6 years; gender: 84F / 48M), who also underwent demographic and lifestyle questionnaires and extensive clinical and neuropsychological assessment, including the Rey Auditory-Verbal Learning Test (RAVLT). We considered successful brain aging individuals without cognitive or functional impairment who scored 9 points in subsection A7 (delayed recall) from the RAVLT, and usual brain aging, cognitively healthy and independent individuals who scored <9 points in the same task. We investigated possible associations between clinical variables, demographics and lifestyle habits with SBA.Results: Among the healthy elderly subjects, 18 (age: 77.3 ± 2.6 years; education: 4.9 ± 3.6 years; gender: 14F / 4M) had a RAVLT delayed recall score 9, while the remaining 114 (age: 79.8 ± 4.5 years; education: 3.0 ± 2.6 years; gender: 70F / 44M) scored < 9 points. Variables significantly associated with SBA in multivariate analysis were younger age (OR: 0.672 - 95% CI 0.462-0.979 for each year less; p = 0.037) and lower scores on the geriatric depression scale (OR: 0.831 - 95% CI 0.688-0.989; p = 0.038) Conclusions: These data suggest an association between younger age and less depressive symptoms with better cognitive performance in this community sample of oldest-old and low schooling individuals. The presence of subjects with such low education classified as SBA suggests a possible participation of biological determinants of SBA.